2004
DOI: 10.17221/467-pps
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Pseudomonas spp. on the development of Botrytis cinerea and Penicillium expansum

Abstract: B��� H., D��� B., S���������� P. (2004): Inhibitory effect of Pseudomonas spp. on the development of Botrytis cinerea and Penicillium expansum. Plant Protect. Sci., 40: 128-134.The influence of antagonistic Pseudomonas spp. on the development of Botrytis cinerea and Penicillium expansum was studied in liquid cultures. Two strains of Pseudomonas spp. (B194 and B224), originally isolated from apple leaves and fruits, respectively, inhibited spore germination and germ tube elongation of B. cinerea or P. expansum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…Most predominant microflora were Bacillus and Pseudomonas sp. This is in conformity with Bryk et al, (2004) who isolated two strains of Pseudomonas sp. (B194 and B224) from apple leaves.…”
Section: Estimation Of Predominant Epiphytes By Fruit Washing Methodssupporting
confidence: 92%
“…Most predominant microflora were Bacillus and Pseudomonas sp. This is in conformity with Bryk et al, (2004) who isolated two strains of Pseudomonas sp. (B194 and B224) from apple leaves.…”
Section: Estimation Of Predominant Epiphytes By Fruit Washing Methodssupporting
confidence: 92%
“…The greatest action of bacteria was observed after 48 h of incubation in mixture of 3:5. These results are in agreement with observations by some researchers (Janisiewicz and Korsten, 2002;Bryk et al, 2004), who demonstrated that P. syringae controlled growth of P. expansum.…”
Section: Antagonism Between Bacterium and Fungussupporting
confidence: 93%
“…The microscopic examination of B. cinerea germinated conidia exposed to FC treatments demonstrated that FC substantially altered morphology of conidia and germ tubes and this effect was linked to the FC concentration. The morphological changes in the germ tubes suggest that the treatment had changed the developmental pattern of the germinating spores, an observation that has been reported in other studies evaluating the effect of synthetic fungicides, NPs or BCAs on fruit pathogens (Jijakli and Lepoivre 1998;Rosslenbroich and Stuebler 2000;Bryk et al 2004;Reglinski et al 2010), although this effect is reported for first time in this study for fatty acid-based NPs. Changes in cell morphology may be due to the characteristics of the viscose FC matrix formed around B. cinerea conidia, which may interfere with Figure 6 Effect of fatty acid-based product Foodcoat (FC) field applications on fungal populations on Sauvignon blanc grape berries at harvest (Marlborough, NZ, 2011).…”
Section: Discussionsupporting
confidence: 77%
“…The morphological changes in the germ tubes suggest that the treatment had changed the developmental pattern of the germinating spores, an observation that has been reported in other studies evaluating the effect of synthetic fungicides, NPs or BCAs on fruit pathogens (Jijakli and Lepoivre ; Rosslenbroich and Stuebler ; Bryk et al . ; Reglinski et al . ), although this effect is reported for first time in this study for fatty acid–based NPs.…”
Section: Discussionmentioning
confidence: 99%